Nations of immigrants Australia and the USA compared - Nieuwenhuysen, J. P.; Higley, John.; Neerup, Stine; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2009)
This timely book examines the immense surges in immigration since the mid-1990s in Australia and the United States, two of the world's most important settler-receiving countries.
1. Introduction / John Higley and John Nieuwenhuysen -- 2. Flows of immigrants 1993-2008 : Australia / Graeme Hugo -- 3. Trends in US immigration / Susan K. Brown, James Bachmeier and Frank D. Bean -- 4. From disordered expansion to disordered stalemate : immigration politics in the United States / Gary P. Freeman -- 5. Immigration policy in Australia / Bob Birrell -- 6. Immigration and the labour market in Australia / Santina Bertone -- 7. Immigration and the United States labour market / Brian Duncan and Stephen J. Trejo -- 8. New groups and social cohesion in Australia / Andrew Jakubowicz -- 9. Latinos, immigration and social cohesion in the United States / David L. Leal -- 10. Immigrant settlement, ethnic relations and multiculturalism in Australia / James Jupp -- 11. Who belongs? : assimilation, integration and multiculturalism in the United States / Cara Wong.
Includes bibliographical references (p. 176-194) and index.
Keywords: Immigrants -- Cultural assimilation -- Australia; Americanization; Multiculturalism -- Australia; Multiculturalism -- United States; Australia -- Emigration and immigration -- Government policy; United States -- Emigration and immigration -- Government policy; Electronic books